2013
DOI: 10.1177/2150129713478846
|View full text |Cite
|
Sign up to set email alerts
|

Using Accounting Proxies of Proprietary FDIC Ratings to Predict Bank Failures and Enforcement Actions During the Recent Financial Crisis

Abstract: Focusing on the recent banking crisis, our article examines whether accounting-based proxies for the Federal Deposit Insurance Corporation’s proprietary CAMELS measurement system effectively predict the likelihood of failure for most regulated, depository institutions with U.S. operations (in and out of sample testing). This article also utilizes regulatory enforcement actions as both an explanatory and predicted variable. The CAMELS ratings from bank examinations are not released to the public because of regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 14 publications
1
31
1
2
Order By: Relevance
“…Kumar & Sayani 3 Kerstein and Kozberg (2013) suggest that the components of the CAMEL model individually and collectively hold the capability of predicting bank failure in the US especially surrounding the recent financial crisis. Hanc (1998) evaluate the importance of various factors in the CAMEL model that cause financial distress to banks and find that internal factors determine the financial health of banks.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar & Sayani 3 Kerstein and Kozberg (2013) suggest that the components of the CAMEL model individually and collectively hold the capability of predicting bank failure in the US especially surrounding the recent financial crisis. Hanc (1998) evaluate the importance of various factors in the CAMEL model that cause financial distress to banks and find that internal factors determine the financial health of banks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gasbarro et al (2002) argues that analyzing soundness of banks during the financial crisis is a challenging task as most indicators of financial health deteriorate in turbulent times. Increased bank failures during 2008 and 2010 imply that financial crises may induce unprecedented changes to financial health of banks, which is not only detrimental to the investors but also affects the economy in general (Kerstein and Kozberg, 2013;Ng and Roychowdhury, 2013). CAMEL indicators and ratings are found to be the most effective determinants of bank failures during the 1985-1992 financial crisis (Cole andGunther, 1995, 1998;Thomson, 1992) and in 2009 (Cole and White, 2012).…”
mentioning
confidence: 99%
“…Equity is a buffer between losses and insolvency when a bank loses money. During the recent financial crisis, failed banks had roughly half the equity cushion of surviving banks (Kerstein & Kozberg, 2013). Bank profitability has been operationalized as the financial statement ratios return on assets (ROA) and return on equity (ROE).…”
Section: Introductionmentioning
confidence: 99%
“…In Appendix VI, we provide a case study that illustrates the source of the Academic studies that have examined the usefulness of CAMELS indicators in predicting bank failures have, by and large, found that they do contain useful information (e.g., Tam and Kiang 1992;Bongini, Claessens and Ferri 2001;Kerstein and Kozberg 2013;Betz, Oprică, Peltonen and Sarlin 2014). Note that these studies do not have the actual CAMELS scores computed by regulators (which are not released).…”
Section: Silver State Bank: a Case Studymentioning
confidence: 99%